Efektivitas DAK Fisik Pendidikan dalam Meningkatkan Kualitas Pendidikan di Sekolah Dasar - Setyawan, Danang Budi; Fahturahman; Nisa, Uliya Khoirun; Putra, Zikalta (Universitas Sarjanawiyata Tamansiswa, 2025)
The Special Allocation Fund for Physical Education (DAK Fisik Pendidikan) is used to develop and finance educational facilities and infrastructure in the regions to improve the quality of education. However, there is currently no relevant evidence to show that DAK Fisik Pendidikan can enhance the quality of education. Therefore, this study aims to determine the effectiveness of DAK Fisik Pendidikan on the quality of education with the parameters of learning quality, literacy, and numeracy. The study uses secondary data from the Ministry of Education, Culture, Research and Technology in 2022 related to data on DAK Fisik Pendidikan, the condition of facilities and infrastructure, and education quality parameters. The data was then analyzed statistically. The results showed that the data did not have a normal distribution so non-parametric tests were conducted. DAK Physical Education has a weak correlation to improving the quality of educational facilities and infrastructure, in this case, the quality of classrooms and library space with a correlation value of r = 0.214. Both the quality of classrooms and library space show a weak correlation with the quality of student learning, literacy and numeracy. The quality of learning has a positive correlation with literacy and numeracy with coefficient values of 0.46 and 0.50 respectively. These findings show that the DAK fisik Pendidikan has little effect on improving the quality of education. This suggests that other factors have a greater influence than the provision of quality educational facilities and infrastructure.